Disaffected democracies : what's troubling the trilateral countries? - Pharr, Susan J.; Putnam, Robert D. (Princeton University Press, 2000)
It is notable that as democracy replaces other forms of governing throughout the world, citizens of the most established and prosperous democracies increasingly report dissatisfaction and frustration with their governments. This volume examines why this is so.